The Afterlife of Daniel Defoe's Captain Singleton in the Seven Years' War. (14th December 2022) - Seager, Nicholas
Abstract: Daniel Defoe's pirate novel Captain Singleton (1720) was republished in 1757, during the political and military crises of the early stages of the Seven Years' War. The fact that Singleton at this time was extensively rewritten has gone entirely unnoticed by scholars. The present article explains how this version of Defoe's maritime picaresque fiction responded to national anxieties about naval performance, aristocratic leadership, and martial masculinity following the loss of Minorca, seeking to galvanize its readers during the privateering rush of this period and the more general appetite for a 'blue-water', colonial war strategy. In 1757, Bob Singleton is transformed from the stateless sea rover of Defoe's original into a patriotic privateer who serves the British nation in an unofficial capacity, both as an African explorer in the first half and a maritime adventurer in the second. The 1757 novel shows the ways in which the rising taste for sentimental fiction, moving away from individualistic adventure stories, coalesced with imperialist and nationalist agendas in the mid-eighteenth century. This example of literary appropriation rewards the investigation of the afterlives of eighteenth-century fiction, aiding recognition of how novels endured and were revived, often in revised or remediated states, to reach different readerships and speak to new sociocultural contexts.